El uso de mapas conceptuales como herramienta educativa en el ámbito de los números racionales - Contreras, Luis C. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
This article is a synthesis of a research carried out as a final project included in a Doctoral Program. The mentioned research consisted of a case study whose goal was to highlight the methodological advantages of conceptual maps in initial diagnosis, instructional design and assessment, as described in the corresponding literature. The identification of rational numbers as those with a finite or periodical decimal representation has been chosen as the specific topic. The individuals were studying the third degree of Teachers’ Training.